Liquid–Liquid Extraction of Hydroxytyrosol, Tyrosol, and Oleuropein Using Ionic Liquids - Romero-Figueroa, J; Merlet-Venturelli, G; Cabezas-Cornejo, R (Taylor and Francis Inc., 2019)
Hydroxytyrosol (HT), tyrosol (TY), and oleuropein (OL) are valuable compounds that can be obtained from olive oil production waste. This study implemented liquid–liquid extraction to obtain HT, TY, and OL from model solutions using two organic solvents, namely, ethyl acetate and n-butyl acetate, and three ionic liquids (ILs), namely, [P6,6,6,14][Tf2N], [P6,6,6,14][DCA], and [omim][Tf2N]. [P6,6,6,14][DCA] showed the best performance, with extraction efficiencies of 92%, 96%, and 83% for HT, TY, and OL, respectively. [omim][Tf2N] showed the highest selectivity in the extraction of TY. Comparisons of the results of a proposed mathematical model with experimental data yielded errors lower than 0.5%. © 2018, © 2018 Taylor & Francis Group, LLC.